Wave scattering by cylindrical obstacle in generalised waveguide - Chumachenko, VP; Petrusenko, IV (IEEE, 2002)
A novel full-wave solution of the problem of electromagnetic wave scattering by a circular post in a straight or continuously curved rectangular waveguide is presented. A rigorous mathematical model is based on the domain-product technique. It allows to construct an efficient series representation for the field in the interaction region. As a result, the initial boundary value formulation is reduced to a matrix equation with the fredholm operator. The last has the form of a sum of several products of the hilbert-schmidt operators provided the post does not touch the boundaries of the interaction region. The kernel matrix operator predetermines the fast convergence of the numerical approximations for a wide range of curvature variation, any possible radius of the cylinder and arbitrary location of the obstacle in the interior of the guide.
International Conference on Mathematical Methods in Electromagnetic Theory (MMET 02) -- SEP 10-13, 2002 -- KIEV, UKRAINE